Polyphenols, Antioxidants, and Wound Healing of Lecythis pisonis Seed Coats - Pimentel, Elisângela Flávia; de Oliveira, Bruno Gomes; Pereira, Ana Claudia Hertel; Figueira, Mariana Moreira; Portes, Danielle Braga; Scherer, Rodrigo; Ruas, Fabiana Gomes; Romão, Wanderson; Fronza, Márcio; Endringer, Denise Coutinho (Planta Medica, 2024)
To better use the Lecythis pisonis Cambess. biomass, this study investigates whether Sapucaia seed coats present wound healing properties. We analyzed the antibacterial, antioxidant, and wound healing-promoting potentials, plus cytotoxicity and stimulation of vascular endothelial growth factor-A. The chemical composition was analyzed by positive ion mode electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry. A total of 19 compounds were identified, such as proanthocyanidin A1, procyanidins A1, B2, and C1, epigallocatechin, and kaempferol (p-coumaroyl) glycoside. Potent antioxidant strength/index was verified for 2,2-diphenyl-1-picrylhydrazyl radical (IC50 = 0.99 µg/mL) and ferric reducing antioxidant power (IC50 = 1.09 µg/mL). The extract did not present cytotoxicity and promoted significant cell migration and/or proliferation of fibroblasts (p < 0.05). Vascular endothelial growth factor-A was stimulated dose-dependently at 6 µg/mL (167.13 ± 8.30 pg/mL), 12.5 µg/mL (210.3 ± 14.2 pg/mL), and 25 µg/mL (411.6 ± 29.4 pg/mL). Platelet-derived growth factor (PDGF) (0.002 µg/mL) was stimulated at 215.98 pg/mL. Staphylococcus aureus was susceptible to the extract, with a minimum inhibitory concentration of 31.25 µg/mL. The identified compounds benefit the antioxidant activity, promoting hemostasis for the wound healing process, indicating that this extract has the potential for use in dermatological cosmetics.
Keywords: Lecythis pisonis Cambess; Lecythidaceae; chemical analysis; wound healing